Studies and Simulations of PbPb Collisions at sNN=2.76 TeV with the Glauber Monte Carlo Model. Issue 1 (1st December 2022) - Zhang, Jiankun; Wang, Lihong; Ni, Ning; Wang, Pengli; Jiang, Xinyun; Liu, Yuxin
Abstract: The main purpose of this paper is to simulate nuclear collisions. We review the theoretical background, experimental techniques, and the phenomena presented and provided by the original Glauber model and experiment. Based on the original Glauber model, we change the data and algorithm to test and compare our model with the original results. Then we figure out the spatial eccentricity of quark gluon plasma in different models and analyze the progress in the Glauber model at collider energies.